Use of Arbitration in the Settlement of Intellectual Property Disputes in Nigeria - Nwogu, Mary Imelda Obianuju (Advances in Social Sciences Research Journal, 2022)
Intellectual Property (IP) protects exclusive ownership, use and/or exploitation of IP rights. The infringement of the said rights give rise to disputes which can be settled by Arbitration. Arbitration is an Alternative Dispute Resolution (ADR) Mechanism, which can be used in the settlement of Intellectual Property (IP) disputes by the agreement of the parties. This method of settling IP disputes is cheaper, faster, more confidential and encourages party autonomy than litigation. Pima facie, IP disputes are arbitrable, though in Nigeria there is no specific law on arbitrability of IP disputes, but there are instances or provisions within the Trademarks Act and Federal High Court Act which permit the deployment of Arbitration to such disputes. WIPO Arbitration and Mediation Centre has settled several mediation and arbitration disputes. The confidential nature of arbitral proceeding has made it particularly advantageous for settling IP cases owing to the delicate nature of the information and documents involved.